2017
DOI: 10.1134/s0006297917030051
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal proinflammatory stress induces accumulation of corticosterone and interleukin-6 in the hippocampus of juvenile rats: Potential mechanism of synaptic plasticity impairments

Abstract: Infectious diseases in early postnatal ontogenesis can induce neuroinflammation, disrupt normal central nervous system development, and contribute to pathogenesis of cerebral pathologies in adults. To study long-term consequences of such early stress, we induced neonatal proinflammatory stress (NPS) by injecting bacterial lipopolysaccharide into rat pups on postnatal days 3 and 5 and then assessed the levels of corticosterone, proinflammatory cytokines and their mRNAs, and neurotrophins and their mRNAs in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…In other studies, the repetitive administration of LPS in low doses induced a delayed decrease in LTP magnitude [8] and learning and memory deficits in rats [64]. The authors have shown that the gene expression levels of neurotrophic factor, BDNF, and its receptor, TrkB, were significantly decreased by LPS treatment, and glutamatergic transmission was attenuated in LPS-treated rats as well [8,64].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…In other studies, the repetitive administration of LPS in low doses induced a delayed decrease in LTP magnitude [8] and learning and memory deficits in rats [64]. The authors have shown that the gene expression levels of neurotrophic factor, BDNF, and its receptor, TrkB, were significantly decreased by LPS treatment, and glutamatergic transmission was attenuated in LPS-treated rats as well [8,64].…”
Section: Discussionmentioning
confidence: 88%
“…The alternative mechanism suggested by Iwai et al [60] is that induced IL-1b inhibits LTP via the activation of p38 MAPK and c-Jun N-terminal kinases (JNK) [61], and that these signal pathways inhibit AMPAR trafficking [62], which is an important mechanism of LTP induction [63]. In other studies, the repetitive administration of LPS in low doses induced a delayed decrease in LTP magnitude [8] and learning and memory deficits in rats [64]. The authors have shown that the gene expression levels of neurotrophic factor, BDNF, and its receptor, TrkB, were significantly decreased by LPS treatment, and glutamatergic transmission was attenuated in LPS-treated rats as well [8,64].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Whereas anti-in ammatory agents primarily improved motivation and anxiety (Raison et al 2013). In addition, induction of depression-like behavior via learned helplessness paradigm resulted in an increased IL-6 expression within the hippocampus (Onufriev et al 2017). Ketamine's antidepressant effect might be through its ability to reduce cytokines in the hippocampus, thus functioning anti-in ammatory (Wang et al 2015).…”
Section: Introductionmentioning
confidence: 99%